PENGARUH CELEBRITY ENDORSER, CITRA MEREK, DAN DISKON TERHADAP MINAT BELI KONSUMEN PADA PRODUK SWETER POLOS DI TAMBORA JAKARTA BARAT - Eko Yuliawan; Mardiah (Jurnal Gici Jurnal Keuangan dan Bisnis, 2021)
Along with the development of the fashion business that is currently continued to be embraced by millennials, the companies engaged in the sale of fashion both large, medium and small began to emerge. The purpose of this study is to analyze and find out if celebrity endorsers, brand image and discounts affect consumers' buying interest in plain sweater products. The data analysis motto used in this study uses multiple linear regression analysis. The sample in this study as many as 385 respondents. The results showed the results of hypothetical tests together (F-Test) celebrity endorser, brand image, and discount together have a positive and significant effect on buying interests. Partial hypothetical test results (t-test) showed that celebrity endorser variables have a positive and significant effect on consumer buying interests of plain sweater products and brand image has a positive and significant effect on consumer buying interests of plain Sweater products.